1-Methyl-3,3-bis[(4-methylphenyl)sulfanyl]piperidin-2-one - Zukerman-Schpector, Julio; Olivato, Paulo Roberto; Cerqueira, Carlos R.; Santos, Jean M.M.; Ng, Seik Weng; Tiekink, Edward R.T. (International Union of Crystallography, 2011)
The piperidone ring in the title compound, C 20H 23NOS 2, has a half-chair distorted to a twisted-boat conformation [Q T = 0.5200 (17) Å]. One of the S-bound benzene rings is almost perpendicular to the least-squares plane through the piperidone ring, whereas the other is not [dihedral angles = 75.28 (5) and 46.41 (5) Å, respectively]. In the crystal, the presence of C-H⋯O and C-H⋯π interactions leads to the formation of supramolecular layers in the ab plane.